The effect of Compton drag on the dynamics of dissipative Poynting-dominated flows: implications for the unification of radio loud AGN - Levinson, A.; Globus, N. (Monthly notices of the Royal Astronomical Society, 2016)
The dynamics of a dissipative Poynting-dominated flow subject to a radiation drag due to Compton scattering of ambient photons by relativistic electrons accelerated in reconnecting current sheets is studied. It is found that the efficiency at which magnetic energy is converted to radiation is limited to a maximum value of ϵc = 3l dis σ0/4(σ0 + 1), where σ0 is the initial magnetization of the flow and l dis ≤ 1 the fraction of initial Poynting flux that can dissipate. The asymptotic Lorentz factor satisfies Γ∞ ≥ Γ0(1 + l dis σ0/4), where Γ0 is the initial Lorentz factor. This limit is approached in cases where the cooling time is shorter than the local dissipation time. A somewhat smaller radiative efficiency is expected if radiative losses are dominated by synchrotron and Synchrotron Self-Compton emissions. It is suggested that under certain conditions magnetic field dissipation may occur in two distinct phases: On small scales, asymmetric magnetic fields that are advected into the polar region and dragged out by the outflow dissipate to a more stable configuration. The dissipated energy is released predominantly as gamma rays. On much larger scales, the outflow encounters a flat density profile medium and re-collimates. This leads to further dissipation and wobbling of the jet head by the kink instability, as found recently in 3D magnetohydrodynamic simulations. Within the framework of a model proposed recently to explain the dichotomy of radio loud active galactic nuclei (AGN), this scenario can account for the unification of gamma-ray blazars with Fanaroff–Riley type I and Fanaroff–Riley type II radio sources.